Accelerating the Education Sector Response to HIV : Five Years of Experience from Sub-Saharan Africa - Bundy, Donald; Patrikios, Anthi; Mannathoko, Changu; Tembon, Andy; Manda, Stella; Sarr, Bachir; Drake, Lesley (World Bank, 2012)
The work described in this review shows the commitment of education teams throughout Africa to contribute to the multisectoral response to HIV/AIDS. It is also a testament to the leadership shown by ministries of education, in helping the new generation of children and youth grow up better able to challenge HIV, and in providing care and support for the educators who often represent more than half the public sector workforce. The work described in this review does not suggest any single solution. Instead, the approach is based on the recognition that Africa is a diverse continent, and countries need to find their own local approaches to the epidemic. The Regional Economic Communities (RECs) of the African Union have been instrumental in encouraging locally specific responses, and recognizing that HIV knows no frontiers, in coordinating responses among neighbors. The countries of East, Central, and West Africa, working through the RECs, have created sub-regional networks of ministry of education HIV/AIDS focal points; these networks have been key to sharing information and developing capacity, and so to accelerating and strengthening responses at the national level. The review shows how, over the last five years, the leadership in ministries of education has been crucial in mobilizing these activities, and also emphasizes that effective implementation depends on the full participation of all stakeholders. Education staff, educators, and learners all have a role to play, as do parent-teacher associations, teachers' unions and the many civil society organizations, including faith-based organizations that are so important in the non-formal sector. The review also demonstrates the commitment of the development partners, and their efforts to harmonize their contribution toward strengthening the education agenda.